Effects of Substitution Gd with La in the Synthesis of GBCO-123 Phase: Gd1-xLaxBa2Cu3O7-? (x=0.05 – 0.50) - Sumadiyasa, Made; Adnyana, I.G.A.P.; Wendri, Nyoman (Journal of Materials Engineering and Processing Technology; Vol 1 No 01 (2017): JOURNAL OF MATERIAL SCIENCE AND PROCESSING TECHNOLOGY (JMSPT), 2017)
It has been conducted a research about the replacement of Gd with La on the phase of GBCO-123: Gd 1-x La x Ba 2 Cu 3 O 7-? (x = 0.0 to 0.5), partially. The compound is called as GLBCO-123 phase. The research aimed is to obtain information about the effects of substitution Gd with La in the Synthesis of GLBCO-123 phase and its particle size. Samples were synthesized by using wet mixing method. The materials used are Gd 2 O 2 , La 2 O 2 , BaO, CuO and nitric acid as a solvent. The characterizations were conducted by XRD and SEM-EDXA. The result showed that the GLBCO-123 phase which contain La<0.25 is in the form of nanoparticle with size of about 96 nm. The volume fraction is decreased with increasing the content of La. Index Terms — GLBCO-123, Gd 1-x La x Ba 2 Cu 3 O 7-? nanoparticle , substitution, volume fraction